2020
DOI: 10.3145/epi.2020.jul.23
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the information and digital competence of Social Sciences students and faculty before and during lockdown due to Covid-19

Abstract: We analyze the perceptions of Social Sciences faculty about their own information and digital competence and that of their students, as well as the changes that have occurred as a consequence of the virtualization of learning caused by the coronavirus pandemic (Covid-19). The methodology used is qualitative, being based on the application of two techniques: discussion groups carried out with experienced faculty from three Spanish universities, and interviews carried out with the same sample after the suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 23 publications
3
35
0
13
Order By: Relevance
“…In Lassoued et al (2020)'s study on obstacles to online learning, the authors identify faculty competence in online assessment and student difficulties in adjusting to online learning as significant barriers to successful e-learning transition. This deficit in mastering online teaching and learning styles is compounded by a lack of faculty and student proficiency in the use of online technologies as discovered in the study on the digital competence of faculty and students at a Spanish university (Sales et al, 2020). This apparent deficit in digital literacy could be due to the absence of institutional support, as suggested in Mouchantaf (2020)'s study.…”
Section: Online Competencementioning
confidence: 98%
See 1 more Smart Citation
“…In Lassoued et al (2020)'s study on obstacles to online learning, the authors identify faculty competence in online assessment and student difficulties in adjusting to online learning as significant barriers to successful e-learning transition. This deficit in mastering online teaching and learning styles is compounded by a lack of faculty and student proficiency in the use of online technologies as discovered in the study on the digital competence of faculty and students at a Spanish university (Sales et al, 2020). This apparent deficit in digital literacy could be due to the absence of institutional support, as suggested in Mouchantaf (2020)'s study.…”
Section: Online Competencementioning
confidence: 98%
“…A Chinese study of four universities revealed that plagiarism was an issue of concern for English language assessment in an online environment (Davies et al, 2020). The fact that many students are aware that copying work without attribution is wrong does not appear to deter many students (Sales et al, 2020). The challenge here for EAP teachers is how to deploy tools such as Turnitin and PeerMark to mitigate instances of online cheating.…”
Section: Academic Dishonestymentioning
confidence: 99%
“…El estudio que presentamos puede servir en el futuro para comparar el tratamiento del que es objeto la formación continua del PDI en PE anteriores y posteriores a la pandemia de la covid-19. La huella de la pandemia en las universidades es patente en el fuerte impulso del que la formación continua del PDI ha sido objeto a nivel internacional para lograr una rápida transición de la enseñanza presencial a la enseñanza online o mixta (cabero almenara y valencia, 2021;allen et al, 2020;corbera et al, 2020;Sales et al, 2020).…”
Section: Conclusionesunclassified
“…Lack of information and digital competence in students is leading to gaps in assessment and inability to effectively communicate, despite mastery of technological tools and extensive use of mobile devices (Sales, Cuevas-Cerveró, & Gómez-Hernández, 2020). Students at a medical school in India were frustrated with online (Zoom-based) flipped classrooms and were requesting a reduction in the number of class sessions to keep up with the space and speed of work online (Roy, Ray, Saha, & Ghosal, 2020).…”
Section: Literature Review Adaptation To Teaching and Learningmentioning
confidence: 99%